Pengaruh Tingkat Pendidikan dan Karakteristik Individu Terhadap Kinerja Karyawan di PDAM Tirta Manakarra Kabupaten Mamuju - Ni Komang Susilawati; Muh. Ilham Wardhana Haeruddin; Muh. Ikhwan Maulana Haeruddin; Siti Hasbiah; Tenri S.P. Dipoatmodjo (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This study aims to determine the effect of the variable Effect of Education Level and Individual Characteristics on Employee Performance at PDAM Tirta Manakarra, Mamuju Regency. The variables used are the level of education and individual characteristics as independent variables and employee performance as the dependent variable. The sampling technique is to use a saturated sampling technique, in which the entire population is sampled. The data collection method in this study was by distributing questionnaires in which the number of respondents was 55 employees. The results obtained in this study are from the t-test statistics showing that the level of education has a significant effect on employee performance in PDAM Tirta Manakarra Mamuju Regency, the value is greater than the value of individual characteristics has a significant effect on employee performance in PDAM Tirta Manakarra Mamuju Regency, the value is greater than Then the value of the F test shows that the level of education and individual characteristics simultaneously have a significant effect on employee performance at PDAM Tirta Manakarra, Mamuju Regency, the value is greater than the value. Furthermore, the results of the analysis of the coefficient of determination show that the level of education and individual characteristics contributes an influence of 89 .2% on employee performance at PDAM Tirta Manakarra, Mamuju Regency.